Estimation and analysis of the price elasticity of demand for different types of beverages in Mexico - Fuentes Castro, Hugo J.; Zamudio Carrillo, Andrés (Estudios Económicos de El Colegio de México, 2014)
The main purpose of this study is proving how using the Household Income and Expenditure National Survey, ENIGH, can deliver contradictory estimations for price elasticities, according to the assumptions made about the goods being analyzed. This work used data for 2008, 2010 and 2012 for making separate estimations about drinking water, bottled juice and soft drinks. The most outstanding case is for soft drinks, which depending on considering or not its size may get an elastic or inelastic figure.